Method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode material
First-principles calculations on carbon-doped crystalline silicon structures address the volume expansion and diffusion issues in silicon-based lithium-ion batteries, improving the theoretical capacity and stability of the negative electrode through structural optimization and lithium diffusion analysis.
Patent Information
- Application Number
- CN202411127618.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-27
AI Technical Summary
Lithium-ion batteries using silicon as a negative electrode material face challenges due to large volume expansion and contraction during charge-discharge cycles, poor conductivity, and low lithium ion diffusion rates, leading to instability and reduced capacity, which are not adequately addressed by existing carbon-doping methods in silicon/graphene or silicon/carbon composites.
Employing first-principles calculations based on density functional theory to study the stability and conductivity of carbon-doped crystalline silicon structures, analyzing structural changes and lithium diffusion behavior at the atomic level, including constructing models, calculating pressure-volume state equations, and performing molecular dynamics to determine diffusion coefficients and energy barriers.
The method enables the design and screening of carbon-doped crystalline silicon for improved lithium-ion battery performance by understanding mechanical and electronic changes, inhibiting volume expansion, and optimizing ion diffusion, thereby enhancing the theoretical capacity and stability of the negative electrode.
Smart Images

Figure CN119207655A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials. Background Art
[0002] Lithium-ion batteries have been widely used due to their large capacity and no memory effect. As electrode materials have an important influence on the performance of lithium-ion batteries, they have been extensively studied. The specific capacity of graphite as a negative electrode material is 372 mAhg -1 , and it is difficult to increase further. The theoretical specific capacity of silicon is 4200mAhg -1 , is considered to be an ideal candidate for negative electrode materials. However, during the charge-discharge cycle of lithium ion insertion and extraction, the lithium-silicon alloy formed by lithiation will cause a large volume expansion. For example, Li 3.75 The formation of Si compounds causes the volume of the material to expand to 300% of its original size, resulting in instability of the solid electrolyte interface film. When lithium ions are extracted during the discharge operation, the large volume shrinkage causes the negative electrode structure to break, resulting in a decrease in its capacity and cycle period, further causing safety issues. At the same time, the poor conductivity and low lithium ion diffusion rate of the silicon negative electrode make it challenging for commercial applications. In order to solve this problem, people have tried to modify the material using methods such as nanotechnology, synthesis and redesign of nanostructures. Among them, doping carbon in silicon is one of the most promising methods. After adding carbon to silicon, the volume expansion of the negative electrode material during charging of lithium-ion batteries can be limited. In addition, carbon doping can also continuously improve the conductivity of the silicon negative electrode. Xiao et al. confirmed that the three-dimensional Si / C composite material prepared by calcination and acid leaching had a capacity of 1700mAhg -1(Xiao CM, Du N, Shi XX, Zhang H, Yang DR. Large-scale synthesis of Si@C three-dimensional porous structures as high-performance anode materials for lithium-ion batteries [J]. Journal of Materials Chemistry A, 2014, 2 (48): 20494-20499.). Researchers develop and design new materials by understanding the lithiation mechanism of electrode materials at the atomic scale. Many studies have reported the diffusion of lithium ions in different silicon materials through calculations, including crystalline silicon, nanowire silicon materials, graphite and graphene. Wan et al. calculated the diffusion barrier of lithium atoms in crystalline silicon, and the calculated value was about 0.58 eV, which is consistent with previous theoretical and experimental results (0.57-0.79 eV) (Wan WH, Zhang QF, Cui Y, et al. First principles study of lithium insertion in bulk silicon[J]. Journal of Physics-Condensed Matter, 2010, 22(41):415501.).
[0003] However, until recently, little attention has been paid to the diffusion of lithium ions in silicon / graphene composites. First principles studies by Chou et al. (Chou CY, Hwang GS. Role of interface in the lithiation of silicon-graphene composites: A first principles study [J]. Journal of Physical Chemistry C, 2013, 117 (19): 9598-9604.) and Zhou et al. (Zhou F, Liao NB, Zhang M, Xue W. Lithiation behavior of graphene-silicon composite as high performance anode for lithium-ion Battery: A first principles study [J]. Applied Surface Science, 2018, 436: 610-615.) found that the silicon / graphene interface can significantly enhance the diffusion of lithium ions. Zhang et al. studied the feasibility of using silicon / carbon multilayer film materials as negative electrodes for lithium-ion batteries, paying special attention to their capacity and diffusion rate (Zhang Z, Liao NB, Zhou HM, Xue W. Insight into silicon-carbon multilayer films as anode materials for lithium-ion batteries: A combined experimental and first principles study [J]. Acta Materialia, 2019, 178: 173-178.). Gao et al. simulated the diffusion of lithium ions in silicon / carbon composite materials, and the results showed that carbon materials promoted the diffusion of lithium ions in silicon materials (Gao X, Lu WQ, Xu J. Insights into the Li diffusion mechanism in Si / C composite anodes for lithium-ion batteries [J]. ACS Applied Materials & Interfaces, 2021, 13 (18): 21362-21370.). The above-mentioned silicon / carbon materials are mainly composed of a silicon layer and a carbon layer.Guifo et al. developed and validated the interatomic reaction potential (ReaxFF) and used it to simulate the nanostructures of various hybrid Si-C systems, providing an atomic-scale understanding of the development of Si-C-based negative electrode materials (Guifo SBO, Mueller JE, Talkhoncheh K, et al. Development and validation of a ReaxFF reactive force field for modeling silicon-carbon composite anode materials in lithium-ion batteries [J]. The Journal of Physical Chemistry C, 2023, 2818-2834.). However, there are few studies on the diffusion of lithium atoms in carbon-doped crystalline silicon structures. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a method for screening the theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium-ion negative electrode materials. The structure and performance of crystalline silicon doped with different concentrations of carbon atoms as negative electrode materials for lithium-ion batteries are studied, and the storage and diffusion behavior of lithium ions in the structure of carbon-doped crystalline silicon are understood at the atomic level, which may be the key to improving the performance of lithium-ion batteries by changing the structure of negative electrode materials.
[0005] The technical solution is to use the first-principles calculation method based on density functional theory (DFT) to study the stability and conductivity of the structure under different carbon doping concentrations, and to calculate and analyze the structural changes of lithium atoms embedded in silicon-based materials. In addition, the diffusion behavior of single lithium atoms in silicon-based structures is also studied.
[0006] The specific technical solutions are as follows:
[0007] A method for screening the theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials, comprising the following steps:
[0008] 1) Constructing models of crystalline silicon and carbon atom-doped crystalline silicon structures;
[0009] 2) Calculate the pressure-volume state equation, density, bulk modulus and tensile stress-strain curve of the structure;
[0010] 3) Calculate the electronic state density of the doped structure and study the electronic structure changes of carbon atom-doped crystalline silicon;
[0011] 4) Constructing a model of lithium embedded in crystalline silicon and carbon doped structure, and performing calculation and analysis to obtain the structural changes and volume expansion rate of crystalline silicon and carbon atom doped structure when the amount of lithium atoms embedded is different;
[0012] 5) Calculate the theoretical specific capacity of crystalline silicon and carbon atom-doped silicon negative electrode materials;
[0013] 6) performing molecular dynamics calculations, embedding a single lithium atom into the gap of the obtained structural model, performing molecular dynamics calculations, and obtaining diffusion coefficients of different doping configurations by calculating mean square displacement;
[0014] 7) Calculate the energy barrier for lithium atoms to diffuse in crystalline silicon, carbon atom-doped crystalline silicon, and silicon carbide crystal structures, and perform bader charge calculation analysis to obtain its diffusion mechanism.
[0015] Furthermore, the specific operation process of step 1) is to construct a supercell containing 64 silicon atoms, then replace 1 to 10 silicon atoms in the doped crystalline silicon with carbon atoms, and select the carbon doping sites in the model based on the principles of lower energy and structural stability.
[0016] Furthermore, the specific operation process of step 2) is to perform structural relaxation and static calculation on the crystalline silicon and carbon-doped crystalline silicon structures to obtain a series of stable crystalline Si-C structure models, obtain their structural information, and calculate and analyze their pressure-volume state equation, density, bulk modulus and uniaxial tensile stress-strain curve, wherein the bulk modulus is obtained by fitting the pressure-volume state equation by the Birch-Murnaghan formula.
[0017] Furthermore, the Birch-Murnaghan formula is used to fit the crystal Si 64-x C x The pressure-volume state equation of the structure gives the bulk modulus of the structure, x = 0, 1, 2, 4, 6, 8, 10:
[0018]
[0019] Where V0 is the equilibrium volume, P is the pressure, V is the volume, B0 and are the first-order derivatives of volume and bulk modulus with respect to pressure, respectively;
[0020] and
[0021] Furthermore, the volume expansion rate before and after the lithium atoms are embedded in step 4) is calculated by the following formula:
[0022]
[0023] V represents the crystalline silicon and Si after embedding Li atoms 64-x C x The volume of the crystal structure, V0 represents pure crystalline silicon and Si 64-x C x The initial volume of the crystal.
[0024] Furthermore, step 5) studies the effect of carbon atom-doped silicon anode materials on the theoretical specific capacity and calculates the lithium formation energy E in the selected structure. f , Lithium E f Calculated by the following formula:
[0025] E f (x) = E(Li x Si 1-y C y )-xE(Li)-E(Si 1-y C y )
[0026] Among them, E(Li x Si 1-y C y ) is the Li atom after insertion x Si 1-y C y The total energy of the structure, x is the number of embedded lithium atoms, E(Li) is the energy of a single atom in a body-centered cubic lithium crystal, and E(Si 1-y C y ) is Si 1-y C y The total energy of the structure.
[0027] Further, the process of obtaining the diffusion coefficients of different doping configurations by calculating the mean square displacement in step 6) is to calculate the diffusion coefficient D of lithium atoms in crystalline silicon, carbon-doped crystalline silicon and crystalline silicon carbide structures according to the Einstein mean square displacement formula:
[0028]
[0029] where r i is the position of atom i, and the brackets indicate the ensemble average over many time origins.
[0030] Furthermore, the specific operation process of step 7) is to calculate the energy barrier for the diffusion of lithium atoms in crystalline silicon, carbon atom-doped crystalline silicon and silicon carbide crystal structures by the Climbing Image Nudging ElasticBand method, and perform bader charge calculation and analysis on the structures of each insertion point on the diffusion path to obtain the diffusion mechanism of lithium.
[0031] The beneficial effects of the present invention are as follows: the present invention obtains the changes in the mechanical properties and electronic structure of the structure when crystalline silicon is doped with different carbon concentrations, and understands the storage and diffusion behavior of lithium ions in the crystalline silicon structure doped with carbon atoms at the atomic level. Through the present invention, the theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon as a lithium ion negative electrode material can be designed and screened, thereby accelerating the development of negative electrode materials for lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic flow chart of a method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium-ion negative electrode materials provided in an embodiment of the present invention;
[0033] Figure 2 The structural models of crystalline silicon, carbon-doped crystalline silicon structure and crystalline silicon carbide in the present invention;
[0034] Figure 3 In the present invention, Si 54 C 10 Comparison of different initial configurations and total energy;
[0035] Figure 4 In the present invention, (a)Si 64-x C x Pressure-volume state equation (x = 0, 1, 2, 4, 6, 8, 10); (b) Si with different carbon concentrations at ambient pressure 64-x C x Structural density; (c) Si 64-x C x The bulk modulus of the structure changes with pressure; (d) crystalline silicon and Si 64-x C x stress and strain curves of structures;
[0036] Figure 5 In the present invention, crystalline silicon, Si 58 C6、Si 54 C 10 and schematic diagram of the electronic density of states of a crystalline silicon carbide structure;
[0037] Figure 6 is the band gap of the crystalline silicon and carbon-doped crystalline silicon structures in the present invention;
[0038] Figure 7 (a) Si under different lithium contents in the present invention 64-x C x The volume expansion rate of the structure, the horizontal axis represents Si6 4-x C x The ratio of lithium ions to original atoms in the structure; (b) Si when 32 and 64 lithium ions are embedded 64 and Si54 C 10 structure;
[0039] Figure 8 In the present invention, crystalline silicon, Si 60 C4 and Si 54 C 10 The formation energy E of lithium in the structure f ;
[0040] Fig. 9 In the present invention, (a) crystalline silicon and Si 64-x C x (a) Diffusion energy barrier and diffusion coefficient of lithium ions at 1000K in crystalline silicon; (b) Difference between the diffusion barrier and bader charge of lithium ions in crystalline silicon, with the inset showing the diffusion path of lithium ions; (c) Difference between the diffusion barrier and bader charge of lithium ions in crystalline silicon carbide, with the inset showing the diffusion path of lithium ions;
[0041] Fig.10 is the diffusion potential energy and the corresponding bader charge along the lithium diffusion path in the present invention; (a) Si 63 There are no carbon atoms on the lithium diffusion path in C1; (b) Si 63 There is a carbon atom on the lithium diffusion path in C1; (c) Si 54 C 10 There is a carbon atom on the lithium diffusion path; (d) Si 54 C 10 There are two carbon atoms in the lithium diffusion path. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited thereto.
[0043] like Figure 1 As shown, a method for screening the theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials comprises the following steps:
[0044] Step 1: Construct a supercell containing 64 silicon atoms, and then replace 1 to 10 silicon atoms in the doped crystalline silicon with carbon atoms. Select the carbon doping sites in the model based on the principles of low energy and structural stability, and on this basis make the doped carbon atoms as evenly distributed as possible in the structure, such as Figure 2 As shown, Figure 2 (a) is crystalline silicon (Si 64 ), Figure 2 (b), (c), (d), (e), (f) and (g) are Si 63 C1、Si 62C2、Si 60 C4、Si 58 C6、Si 56 C8 and Si 54 C 10 ,and Figure 2 (h) is crystalline silicon carbide (Si 32 C 32 ). In each doping concentration model, the present invention attempts different configurations to perform structural optimization to extract energy values, and selects the configuration with the lowest energy for subsequent lithium insertion calculations. Figure 3 Listed crystalline Si 54 C 10 Structural models of different doping sites, choose the one with the lowest energy Figure 3 The performance of the model (a) in Figure 1 was analyzed after the lithium atoms were embedded. The electronic structure of other structural models with higher energy and their influence on the lithium diffusion characteristics were also studied. The results were consistent with the model selected in this paper, so this paper selected the configuration of this doping site to explore the structural changes after the lithium ions were embedded and the diffusion mechanism of lithium ions.
[0045] Step 2: Set the model-related calculation parameters: Use the VASP (Vienna Ab-initio Simulation package) software package, use the projected augmented wave (PAW) potential with a plane wave cutoff energy of 400 eV, calculate the Brillouin zone using a 4×4×4 k-point grid, and fully optimize the atoms and unit cell until the calculated Hermann-Feynman force is less than 0.01 eVA -1 , the energy convergence standard is 10 -5 eV. The structure of crystalline silicon and carbon atom-doped crystalline silicon was optimized and statically calculated under pressure of 0-20 GPa. The pressure-volume state equation, density change, bulk modulus and tensile stress-strain curve were obtained by calculation and analysis. The results are as follows Figure 4 As shown in (a) in the figure, although the molar mass of carbon atoms is smaller than that of silicon atoms, the Si-C covalent bond formed by doping carbon atoms is stronger and will enhance the charge transfer between atoms in the structure. For example, the Si-Si bond length between atoms in the crystalline silicon structure is about The Si-C bond length in the carbon atom-doped crystalline silicon structure is approximately Therefore, the volume of the structure decreases and the bulk modulus increases. Figure 4 As shown in (b) in Figure 1, the density of carbon atom-doped crystalline silicon structure increases with the increase of carbon concentration. Figure 4 From (c) in Fig. 1, it can be seen that the bulk modulus of the structure also increases with the increase of the concentration of doped carbon atoms. Figure 4From the tensile stress-strain curve shown in (d), it can be seen that the elastic modulus of the structure increases with the increase of the concentration of doped carbon atoms. However, the tensile limit of the carbon-doped structure is less than that of pure crystalline silicon.
[0046] Step 3: Calculate the electronic state density of crystalline silicon and carbon-doped crystalline silicon structures. Figure 5 and Figure 6 As shown in Figure 1, although density functional theory calculations usually underestimate the band gap values of insulators or semiconductors, qualitative results of the influence of doping effects on electronic structure can still be obtained through this calculation, that is, doping with carbon atoms can reduce the electronic band gap of crystalline silicon-based structures and improve their conductivity. For example, Si doped with 3.1% carbon atoms 62 The band gap of C2 structure is 0.50eV, while Si 58 C6 and Si 54 C 10 The band gap of the structure is reduced to 0.35eV and 0.20eV respectively. In contrast, the band gap value of crystalline silicon carbide is 1.52eV. This shows that the band gap of the carbon-doped crystalline silicon structure is not only related to the concentration of the doped carbon atoms, but also to its geometric configuration. Figure 5 From the electron state density of the structure shown, the highest occupied atomic orbital (HOAO) mainly comes from the Si_3p orbital, while the lowest unoccupied atomic orbital (LUAO) comes from the Si_3p and Si_3s orbitals. For the carbon-doped crystalline silicon structure, the HOAOs come from both the Si_3p and C_2p orbitals. After doping with carbon atoms, the LUAOs shift to lower energy, resulting in a smaller band gap. At the same time, the LUAOs mainly come from carbon atoms as well as silicon atoms, which indicates that the reduction in the band gap is caused by the interaction between the Si-C covalent atoms, rather than the inherent properties of the doped carbon atoms.
[0047] In this embodiment, an 8×8×8 k-point grid is used to sample the Brillouin zone.
[0048] Step 4: Construct a model of lithium ion embedding into crystalline silicon and doping structure, and calculate the structure after lithium ion embedding. Figure 7 The volume expansion rate of crystalline silicon and carbon atom doped structures when different lithium ion embedding amounts are shown, as well as the volume expansion rate of Si when 32 and 64 lithium atoms are embedded. 64 and Si 54 C 10 That is, the doping of carbon atoms can inhibit the volume expansion of the structure. The higher the concentration of carbon atoms, the better the structural inhibition effect. Especially when the ratio of embedded lithium ions is less than 0.3, doping with carbon atoms can better inhibit the volume expansion of the crystal structure during lithiation. For example, at low lithium concentrations, the volume of the crystal Si 56 C8 and Si 54 C 10The volume of the structure hardly expands. Figure 7 As can be seen in (b), the covalent bond network structure of the silicon-based structure changes when a high concentration of lithium ions is embedded. When more than 32 lithium ions are embedded in the structure, that is, when 50% of the lithium ions are embedded, the Si-C and Si-Si covalent bond structures begin to dissociate, causing the crystal structure to transform into an amorphous structure. When the number of embedded lithium ions increases to 64, that is, the proportion of embedded lithium ions is 100%, the Si-C and Si-Si covalent bond structures further dissociate, and the covalent bond network no longer exists.
[0049] Step 5: Calculate the crystalline silicon and Si 60 C4 and Si 54 C 10 The formation energy E of lithium in the structure f , Figure 8 As shown in the figure, with the initial lithium insertion, the formation energy increases with the number of embedded lithium ions. At the turning point, the formation energy begins to decrease, indicating that the structure has reached the theoretical lithium ion storage limit, and the theoretical specific capacity can be calculated based on this. The results show that the theoretical specific capacity of crystalline silicon is 3713mAhg -1 , while crystal Si 60 C4 and Si 54 C 10 The theoretical specific capacity of the structure is slightly reduced, which is 3445mAhg -1 and 2977mAhg -1 , the decrease in specific capacity is due to the dense stacking of silicon-carbon structure induced by carbon doping.
[0050] Step 6: Perform first-principles molecular dynamics calculations continuously in the temperature range of 300K to 1000K at a temperature interval of 100K. The diffusion coefficients of lithium ions in crystalline silicon and carbon-doped crystalline silicon structures are obtained according to MSD calculations, such as Fig. 9 As shown in (a), the diffusion coefficient of lithium decreases with the increase of the concentration of doped carbon atoms.
[0051] Step 7: Calculate the energy barrier for the diffusion of lithium ions in crystalline silicon, carbon atom-doped crystalline silicon, and silicon carbide crystal structures. The results show that the diffusion barrier for lithium increases with the increase in the concentration of doped carbon atoms. Obviously, the increase in the diffusion energy barrier leads to a decrease in the diffusion coefficient. The diffusion of lithium atoms in the carbon atom-doped crystalline silicon structure is inhibited. This may be because the Si-C covalent bond is stronger than the Si-Si covalent bond, resulting in a denser structure, thereby narrowing the diffusion channel for lithium ions in the structure. In order to further understand the effect of doped carbon atoms on the diffusion behavior of lithium in the structure, the present invention compares the diffusion results of lithium ions in crystalline silicon and crystalline silicon carbide, and performs bader charge calculations on the structures of each insertion point on the diffusion path, such as Fig. 9As shown in (b) and (c) in Figure 1, the diffusion barrier of lithium ions in a pure crystalline silicon structure is about 0.58 eV, while in a crystalline silicon carbide structure it is as high as 1.89 eV. Fig. 9 (b) and 9(c) show the diffusion path of lithium ions in crystalline silicon and crystalline silicon carbide. In crystalline silicon, the most stable position for lithium ions to be embedded is the gap at the center of the tetrahedron, where the nearest neighbor distance Si-Li to the silicon atom is In crystalline silicon carbide, the most stable position for lithium ion embedding is the gap at the center of a tetrahedron composed of four carbon atoms. At this time, the nearest neighbor distance Li-C to the carbon atom is The transition position along the diffusion path is the gap of a tetrahedron composed of four silicon atoms. At this time, the nearest neighbor distance Li-Si to the silicon atom is And choose crystal Si 63 C1 and Si 54 C 10 The doping structure model calculates several different diffusion paths in its structure, such as Fig.10 As shown, the diffusion mechanism of lithium in carbon-doped silicon-based structures was obtained, that is, the doping of carbon atoms leads to a denser stacking of the Si-C structure, the narrowing of the diffusion channel increases the diffusion energy barrier of lithium ions, and there is a strong correlation between the electron loss of lithium ions and the potential energy on the diffusion path. The greater the electron loss, the lower the potential energy, and vice versa.
Claims
1. A method for screening the theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium-ion negative electrode materials, characterized in that: The steps include: 1) Constructing models of crystalline silicon and carbon atom-doped crystalline silicon structures; 2) Calculate the pressure-volume state equation, density, bulk modulus and tensile stress-strain curve of the structure; 3) Calculate the electronic state density of carbon-doped crystalline silicon structure and understand the electronic structure changes of carbon-doped crystalline silicon; 4) constructing a model of the structure of lithium embedded in crystalline silicon and carbon atom doped crystalline silicon, and performing calculation and analysis to obtain the structural changes and volume expansion rates of crystalline silicon and carbon atom doped crystalline silicon with different amounts of lithium atoms embedded; 5) Calculate the theoretical capacity of crystalline silicon and carbon atom-doped crystalline silicon negative electrode materials; 6) Perform first-principles molecular dynamics calculations to embed single lithium ions into the gaps of crystalline silicon and carbon atom doped structure models, and obtain the lithium diffusion coefficients of different doping configurations by calculating the mean square displacement; 7) Calculate the energy barrier for lithium ion diffusion in crystalline silicon, carbon-doped crystalline silicon, and silicon carbide crystal structures, and perform charge transfer analysis to explore the lithium ion diffusion mechanism.
2. A method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials as claimed in claim 1, characterized in that: The specific operation process of step 1) is to construct a supercell structure model containing 64 silicon atoms, then replace 1 to 10 silicon atoms in the doped crystalline silicon with carbon atoms, and select the carbon doping sites in the model based on the principles of lower energy and structural stability.
3. A method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials according to claim 1, characterized in that: The specific operation process of step 2) is to perform structural relaxation and static calculation on the crystalline silicon and carbon-doped crystalline silicon structures to obtain a series of stable crystalline Si-C structure models, obtain their structural information, and calculate and analyze their pressure-volume state equation, density, bulk modulus and uniaxial tensile stress-strain curve, wherein the bulk modulus is obtained by fitting the state equation by the Birch-Murnaghan formula.
4. A method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials according to claim 3, characterized in that: The Birch-Murnaghan formula was used to fit the crystalline Si 64-x C x The pressure-volume equation of state of the structure gives the bulk modulus of the structure, x = 0, 1, 2, 4, 6, 8, 10: Where V0 is the equilibrium volume, P is the pressure, V is the volume, B0 and are the first-order derivatives of volume and bulk modulus with respect to pressure, respectively; 5. A method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials according to claim 1, characterized in that: The volume expansion rate before and after the lithium ion is inserted in step 4) is calculated by the following formula: V represents the crystalline silicon and Si after lithium ion embedding 64-x C x The volume of the crystal structure, V0 represents pure crystalline silicon and Si 64-x C x The initial volume of the crystal.
6. A method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials according to claim 1, characterized in that: Step 5) The effect of carbon atom doping on the theoretical capacity of silicon anode materials was studied, and the lithium formation energy E was calculated in the selected structure. f , Lithium E f Calculated by the following formula: Ef(x)=E(LixS11-yCy)xE(Li)-E(Si1-yCy) Among them, E(LixSi 1-y Cy) is LixSi after lithium ion embedding 1-y The total energy of the Cy structure, x is the number of embedded lithium ions, E(Li) is the energy of a single atom in a body-centered cubic lithium crystal, and E(Si 1-y Cy) is Si 1-y Total energy of the Cy structure.
7. A method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials according to claim 1, characterized in that: The process of obtaining the diffusion coefficients of different doping configurations by calculating the mean square displacement described in step 6) is to calculate the diffusion coefficient D of lithium ions in crystalline silicon, carbon-doped crystalline silicon and crystalline silicon carbide structures according to the Einstein mean square displacement formula: where r i is the position of atom i, and the brackets indicate the ensemble average over many time origins.
8. A method for screening theoretical capacity and ion diffusion performance of carbon-doped crystalline silicon-based lithium ion negative electrode materials according to claim 1, characterized in that: The specific operation process of step 7) is to calculate the energy barrier for the diffusion of lithium ions in crystalline silicon, carbon atom-doped crystalline silicon and silicon carbide crystal structures by the Climbing Image Nudging Elastic Band method, and perform bader charge calculation analysis on the structure of each insertion point on the diffusion path to obtain the diffusion mechanism of lithium.
Citation Information
Patent Citations
Method for testing performance regulation and control of cobalt-doped molybdenum boride lithium ion battery and application of cobalt-doped molybdenum boride lithium ion battery
CN118443531A
